The domestication and the brain: forty years after - N. K. Popova (Вавиловский журнал генетики и селекции)
The domestication of animals was crucial for the civilization evolutionary experiment. The main characteristic of domesticated animal is tame behavior towards man. D.K. Belyaev suggested that the domestication was carried out by man of the Stone Age as unintended selection of nonaggressive animals. This hypothesis was confirmed at the Institute of Cytology and Genetics, Novosibirsk, by unique long-lasting selection of silver foxes, Norway rats and American minks for nonaggressive behavior towards man. The review concentrates on the role of the brain neurotransmitters in the mechanism of animal domestication. Specifically, it describes the effect of selective breeding for nonaggressive behavior on the brain neurotransmitter serotonin (5-HT) system. Our data showed that produced by domestication the conversion of wild, aggressive animal to non-aggressive towards man is associated with changes in the expression of key molecular members determining the brain 5-HT system functioning. Significant difference between aggressive and nonaggressive animals in the 5-HT metabolism, in the expression of principle metabolic enzymes and 5-HT receptors was shown in different species of mammals (silver foxes, Norway rats and American minks). Higher concentration of 5-HT and its metabolite, 5-hydroxyindoleacetic acid, increased activity of the principle enzyme in 5-HT synthesis (tryptophan hydroxylase-2) and decreased activity of the principle enzyme in 5-HT degradation (monoamine oxidase A) was shown in the midbrain of domesticated silver foxes and rats. The expression of the 5-HTA receptor gene, the density and functional activity of 5-HTA receptors in nonaggressive rats were increased. The review provides converging lines of evidence for our hypothesis that the changes in the brain 5-HT contributes to a mechanism underlying correlative patterns of domestication, i.e. changes in the pivotal for stress response and for the reproduction pituitary-adrenal and pituitary-gonadal systems.